Construction techniques for cross-sea bridges in coral reef and island environments - Zhong, Yu; Zhang, Yongtao; Yu, Chengcheng; Ji, Fuquan; Chen, Peishuai (Frontiers in Earth Science, 2025)
Coral islands and reefs serve as the sole land-based foundations in the open ocean, and their unique engineering characteristics pose significant challenges for cross-sea bridge construction. This study focused on the China-Maldives Friendship Bridge to investigate the load-bearing mechanisms and construction techniques of pile foundations on coral islands and reefs. Field and laboratory tests on coral reef debris and reef limestone yielded a method to evaluate the compactness of coral reef debris using dynamic penetration test (DPT) blow count. Different classification methods were employed to perform engineering classification and evaluation of the coral reef debris and reef limestone strata. Shear tests on the coral reef debris-pile interface and model tests on driven steel pipe piles clarified the mechanism underlying low pile side friction resistance in coral reef debris strata, while a modified formula for calculating side friction resistance was provided. Shear tests of reef limestone-concrete interfaces with different surface morphologies, combined with field pile testing, yielded recommended mobilization coefficient (c2) of side friction resistance for cast-in-place piles in reef limestone strata. A hydraulic automatic opening and closing chuck for driven piles, a large cantilever guiding frame system with a fuse mechanism, and specialized drilling heads for cast-in-place piles, were developed to ensure pile construction quality.